Perbandingan Constitutional Theory Dalam Doktrin Para Ahli Sebagai Bentuk Landasan Kelembagaan Negara - Aini Shalihah; Fahrizal Nur Mahalli; Ahmadi (Sosio Yustisia: Jurnal Hukum dan Perubahan Sosial, 2023)
The constitution is basically a set of rules that regulate and shape the organs of government and their authorities, as well as the foundations of the state. The constitution functions in maintaining the stability and continuity of political and legal structures as well as the basic principles that serve as guidelines and are formulated in written form. This paper will analyze the comparison of constitutional theory in the doctrine of experts as a form of state institutional basis. With a comparative study between each character, the results of this paper aim to add to the body of knowledge about the world's constitutional theory. Broadly speaking, the constitution is the basic law which is then used as a guide in the administration of a country and there are also two kinds of constitutions, namely written constitutions and also unwritten constitutions. Regarding this matter, the author will analyze how the concept of constitution and state institutions from C.F. Strong, K.C. Wheare, Henc vam Maarseveen as well as from Pancasila law state thinkers (Indonesia) such as Jimly Asshiddiqie and Bagir Manan. This paper uses normative legal research methods using a comparative approach and a conceptual approach. The results of the discussion show that C.F.Strong's concept of state institutions states that the general attributes that must be owned by a modern constitutional state must have branches of legislative, executive and judicial powers. Then K.C. Wheare and Henc van Maarseveen stated that the constitution forms the main institutions of government, such as the legislature, executive and judiciary, while the determination of the composition and method of appointing these institutions is often left to ordinary law. Then, the concept of the Indonesian constitution that state institutions that have been contained in the Indonesian constitution have actually been the result of transformations from world doctrines such as the concepts of C.F.Strong, K.C.Wheare, and Henc van Maarseveen and several other figures. Although, not in its entirety, the theories that have been put forward have become reference material in forming a state institutional structure that is in accordance with the circumstances and form of the state.